Military Organizations Can Walk and Chew Gum at the Same Time. Issue 2 (April 2022) - Talbot, Steven; Fischer, Tiffany
This article is a response to a recent publication by Hasselbladh and Ydén in this journal, entitled "Why Military Organizations Are Cautious About Organizational Learning?" Through their use of dichotomous logic, the authors argue continuous learning poses a threat to the functioning of military organizations. The following commentary argues for a necessary coexistence between the mainstays of the traditional bureaucratic military organization presented by Hasselbladh and Ydén and continuous learning required by military organizations to compete and cope with technological advancements and gray zone challenges afforded by the modern operating environment.